2016
DOI: 10.15406/frcij.2016.02.00060
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Biochemical Effects of Acute & Chronic Tramadol drug Toxicity on Liver, Kidney and Testicular Function in Adult Male Albino Rats

Abstract: Background: Tramadol is becoming abused among teens; especially between males. The study aimed to investigate the histopathological and biochemical profiles of acute and chronic toxic effects of tramadol on hepatic, renal and testicular functions.Methodology: Sixty male adult albino Sprague-Dawley rats were used. Rats were divided into three groups. Group I: control. Group II: representing acute tramadol toxicity and group III: representing tramadol dependent use for 60 days.Results: Group II displayed hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 26 publications
7
21
0
Order By: Relevance
“…Other observation in the current study is MNCs infiltration in the renal cortex around degenerating tubules giving a picture of interstitial nephritis, this finding is in agreement with previous studies 9,10,15 , and this finding in addition to the other findings can be reflected as a sign of renal damage as described by Muslim Z, 2018 16 while is in conflicts with this finding by Zaghlol et al, 2018 11 and Ali et al, 2018 17 and this might be due to small dose or small dose plus short period, respectively. The hyaline cast seen within the degenerating tubules is another finding in the present study which ascribed to the solidification of Tamm-Horsfall mucoprotein, that secreted by the renal tubular cells.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Other observation in the current study is MNCs infiltration in the renal cortex around degenerating tubules giving a picture of interstitial nephritis, this finding is in agreement with previous studies 9,10,15 , and this finding in addition to the other findings can be reflected as a sign of renal damage as described by Muslim Z, 2018 16 while is in conflicts with this finding by Zaghlol et al, 2018 11 and Ali et al, 2018 17 and this might be due to small dose or small dose plus short period, respectively. The hyaline cast seen within the degenerating tubules is another finding in the present study which ascribed to the solidification of Tamm-Horsfall mucoprotein, that secreted by the renal tubular cells.…”
supporting
confidence: 94%
“…50mg/kg b.wt produced the same degree of degeneration after treating animal for only two weeks as reported by Hafez et al,2015. 14 Also such tubular epithelial injuries induced by tramadol was reported by many studies. [9][10][11] The mechanism of tubular damage of the renal tubules is particularly due to sensitivity of renal tubules to toxic effects, in part since they have high consumption of O 2 and weak enzyme system. 13 On the other hand a study done by Atici et al, 2005 15 indicated that the risk of increased level of lipid peroxidation and renal damage after prolonged use of opioids, particularly morphine in the rat's kidney.…”
mentioning
confidence: 99%
“…48 - 50 On the contrary, levels of AST, ALP, ALT, TB, CB and MDA were increased significantly (p<0.05) whereas SOD, CAT and GSH levels were decreased significantly (p<0.05) in TD-treated rats in comparison to control ( Table 3 - 5 ).Similar observations have been reported in previous studies. 51 , 52 The microscopic examination of the liver of NAC and MT-treated rats showed normal architecture; however, the liver of TD- treated rats showed necrosis of hepatocytes ( Figure 1 - 4 ). The observed histological alterations in the liver of TD-treated rats are in conjunction with earlier findings.…”
Section: Resultsmentioning
confidence: 98%
“…Tramadol is one of the opioid drugs that is extensively used as a pain-killer for chronic pain and cancers [10]. However, multiple tissue toxicities were reported for patients consuming tramadol medication several times a day [13][14][15][16][17]. Since tramadol like other opioids induces oxidative stress which alters cell structure causing apoptosis [21][22][23][24][25], the pomegranate was used in the current study as a protective agent based on its antioxidant activity [34,35,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol is used to reduce pain resulted from posttraumatic, obstetric, osteoarthritis, fibromyalgia, renal, biliary colic, and neuropathic pain [12]. However, multiple tissue toxicities were reported when tramadol was administrated [13][14][15][16][17], especially for patients consuming tramadol medication several times daily to relieve chronic pain. We and others have shown that tramadol induces testicular toxicity in adults [5,9,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%